Contextual integration in waterfront development - Abdul Latip, Nurul Syala (2011)
The relationship between waterfronts and water in the establishment of many cities is undeniable. Issues as to why many waterfront developments do not respond to their water are often raised. This thesis examines the response of waterfront development towards its water (in particular the urban rivers). This is measured through the level of contextual integration in the city centre of Kuala Lumpur to identify the reason why this situation exists. The research employed the qualitative method using a case study approach. It triangulates several techniques, which include morphological study, field observations (visual survey, direct observation, activity mapping), focus groups and in-depth interviews. The theoretical framework was based on the Integrative Theory of Urban Design, which has five main principles comprising ‘good form’, ‘legibility’, ‘vitality’, ‘comfort’ and ‘meaning’ from which thirteen attributes were extracted. The research found a mix of levels in the contextual integration of the KL waterfront for all attributes evaluated. Five attributes that affect the level of contextual integration the most are the ‘direct access’, ‘physical character of urban river’, ‘seating’, ‘development that addresses urban river’ and ‘shade’. This study inferred that the other related attributes borrowed from other public spaces are vital to achieve the response of waterfronts towards the urban river. However, the evaluation criteria have to be suited to the local context. Twenty-one factors were identified that affect the level of contextual integration. Three reoccurring factors in seven out of the thirteen attributes evaluated are ‘the existence of highway’, ‘fenced private property till the edge of the river’ and ‘building built abutting the river edge’. It also gathered that the contextual integration between the waterfront and the urban river can only be achieved with the interrelation of the physical and functional dimensions. Eight key reasons were established as to why the waterfront is not contextually integrated with the urban river, these are i) lack of planning – policies, laws, guidelines, master plan, ii) limitation of funds, iii) condition of the river, vi) introduction of other transportation systems, v) lack of coordinated management, vi) political will, vii) lack of awareness and viii) market demand. These findings contribute to the gap in many queries and assumptions concerning this issue from the perspective of a city centre in an emerging Asian country.